Minority v minoritě a národnostní školství - Nosková, Helena (Lidé města, 2000)
ln the introduction the author looks at the position of Slovaks in the Czech Lands, whether they form an ethnic minority or whether they are subject to assimilation in the Czech environment. On the strength of data from field research she proves that modem ethnic minorities have lost the attributes which were signs of their ethnic life in the past. Given many changes in whole communities and the economic system, transformation of social structures, the demographic structure as well as migration movements there was the emergence of other minorities - cultural, social, and professional. She stresses that in the latter two new minorities there has been an interplay of minorities with the majority society, which has brought about acceleration integration. The researcher also pays attention to the specificities of Slovaks in Bohemia and arrives at the conclusion that differences were and still are given facts, that a substantial part of Slovaks has not moved to Bohemia from Slovakia, but from other countries such as Romania, Hungary, Yugoslavia, Subcarpathian Ruthenia and France. Just these fellow countrymen gave rise to significant cultural minorities in some Czech and Moravian regions which had a different cultural background than Slovaks coming to Bohemia directly from Slovakia. Moreover, they had their own ideas about the education of their children and their life in the Czech and Moravian environment. In the next part the author pays attention to the activities of Slovak politicians which focused on the creation of a certain status of Slovaks in Bohemia. They were to acquire the character of Slovak ethnic minority, although they were living on the territory of their own country. She explains why this intention was not fulfilled in the past and why it is being implemented at present. She analyzes the issue of ethnic education, centering not only on Slovaks, but also on the education in maternal tongue in the environrnent of the Gerrnan, Polish, Romany and Greek minorities. She brings information about the relevant civic associations of ethnic minorities and their work.